Special Issue on Nordic Perspectives on Play and Playful Approaches to Pedagogy, Teaching and Learning - Helle Marie Skovbjerg; Elin Eriksen Ødegaard; Ole Lund; Mona Have; Helle Hovgaard Jørgensen; Vibeke Schrøder; Sisse Oreskov; Mikkel Snorre Wilms Boysen (Nordisk tidsskrift for pedagogikk og kritikk, 2024)
There has been a flourishing of interest in recent years in the positive contribution of play and playfulness to the everyday lives of children and young people, as well as to their life at school and as students.